The aesthetics of the fantasy narrative in the war novel )The flask woman's novel as a model( - إسماعیل, دیما; میا , فاخر; محمد مروشيه (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Summary Various modernist terms have entered our modern Arab literature in the recent period, and the term fantasy emerged from it, this term that entered the world of the Arab novel in all its forms, including the war novel , so it was an influential factor in the narrative by transporting it (Narration transfer) to a new world familiar characterized by artistic and aesthetic elegance, through the element of suspense that it raises at the recipient. The research deals with fantasy as a term (meaning leaving the real world to the world of non-reality: the world of imagination) and studies the aesthetics of this artistic color in the narrative in the novel The Woman of the Bottle by Salem Matar) in depth in the aesthetic aspect within the narrative in all its aspects and in a detailed manner.